2021
DOI: 10.1186/s40545-021-00362-3
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions from pharmaceutical stakeholders on how the pharmaceutical budget is allocated in South Africa

Abstract: Background South Africa faces a heavy burden of disease, which impacts resource allocation. The needs of South Africa require efficient translation into pharmaceutical expenditure for medicine provision, to ensure availability of medicines. Given that South Africa faces various challenges with medicine provision accompanied by rising pharmaceutical expenditure, this study aimed to report on the considerations and methods used to determine the healthcare budget for South Africa, and how it is tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(11 citation statements)
references
References 4 publications
0
11
0
Order By: Relevance
“…Nsabagasani and colleagues studied how Uganda responded to the 2012 WHO recommendations on child-appropriate dosage formulations and identified weak institutional capacity in convening relevant stakeholders to assess how the country could move forward in adopting the recommendations [ 39 ]. In addition, technical advisory committees could have a wider mandate or longer-term role [ 16 , 18 , 41 ], with a study from Ghana suggesting the committees could have a role in advocating for greater adherence to NMLs [ 18 ]. To improve implementation, more attention to adherence and compliance strategies could be achieved through better coordination and oversight by scientific selection committees.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Nsabagasani and colleagues studied how Uganda responded to the 2012 WHO recommendations on child-appropriate dosage formulations and identified weak institutional capacity in convening relevant stakeholders to assess how the country could move forward in adopting the recommendations [ 39 ]. In addition, technical advisory committees could have a wider mandate or longer-term role [ 16 , 18 , 41 ], with a study from Ghana suggesting the committees could have a role in advocating for greater adherence to NMLs [ 18 ]. To improve implementation, more attention to adherence and compliance strategies could be achieved through better coordination and oversight by scientific selection committees.…”
Section: Resultsmentioning
confidence: 99%
“…Enforcement strategies and policy controls from health authorities are crucial factors affecting the prescribing and availability of medicines prioritized by NMLs [ 16 , 20 , 42 , 43 ]. Key factors preventing effective implementation can be the lack of an enforceable regulatory or legislative framework supporting compliance to NMLs, including linkages to pharmaceutical services departments [ 41 ]. Odoch and colleagues found that domestic health changes such as the devolution of health services had influenced NML updates [ 16 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations